TRAVEL MEDICINE MANAGEMENT FOR THE ANTICIPATION OF INFECTIOUS DISEASES IN SOUTHEAST ASIA: A SYSTEMATIC REVIEWÂ - Dewi, Ni Putu Ayu Prima; Bachtiar, Adang (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Travelling abroad have various health risks such as sudden and significant changes in altitude, humidity, temperature and exposure to a variety of infectious diseases. Travel medicine concept is needed to provide information to professional health services not only on risk of infectious diseases but also to ensure the personal safety of travellers and to minimize environmental risk during travel. The Objective of this study is to investigate the practices of travel medicine management for the anticipation of infectious disease spread by travellers. Methods: This study used systematic literature review based on PRISMA (Prefered Reporting Items for Systematic Reviews & Meta-Analyses)protocol to identify all the published articles using relevant keywords.We searched in Scopus (Elsevier), Science direct (Web of Science), Cochrane library and Pubmed. Period of study was between 2005 and 2018. In total, there were eight studies that discussed travel medicine management regarding the anticipation of infectious diseases in Southeast Asia, which includes the spread and narrative synthesis. Results: From 126 authors finally include 8 papers in this review. Almost all of the management of travel medicine can reduce the risks of travel-related diseases. The travel medicine management explained how to effectively prevent the spread of infectious diseases, for example dengue, malaria, rabies, zika virus, diarrhea and respiratory syndrome. Those diseases can easily spread when the travellers body immunity decreases or when they are exhausted during the trip. Thus, it is necessary for the travellers to anticipate the spread of diseases by knowing the information of particular diseases in a country or a region that will be visited and having prophylaxis or vaccination before travelling. Conclusions: The travel medicine management can significantly impact on the anticipation of infectious diseases spread by travellers since the practices require the latest facts and information about the epidemiology of infectious health risks worldwide.The recommendation for future research is to review more travel medicine management studies in order to get deeper understanding.For Policy maker, it is suggested to design policy to improve and updating knowledge.